2020
DOI: 10.1108/mip-03-2020-0101
|View full text |Cite
|
Sign up to set email alerts
|

A new frontier: alcohol sponsorship activation through esports

Abstract: PurposeThe purpose of this paper is to examine the impact of alcohol sponsorship-linked advertising through esports upon young gaming audiences and how gaming behaviours affect advertising response.Design/methodology/approachA cross-sectional survey study was employed to examine the prevalence and nature of alcohol advertising in esports, and the impact of esports participation upon young audiences' consumption and preferences concerning alcohol. Survey data were collected from 976 young Australian gamers aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 77 publications
0
9
0
Order By: Relevance
“…There is little research on the impacts of gaming on healthy lifestyle behavioral factors, including sedentary behavior, diet, and effective mitigation strategies. Given that obesity and associated adverse health issues are a critical priority for health policy makers globally, and there is evidence of growing sponsorship of esports and in-game product placement by harmful product categories such as alcohol, gambling, and junk food (Kelly and Van der Leij, 2020), research considering the well-being impacts of gaming is needed. Diet and metabolic risks have risen as leading drivers of diseases (Gakidou et al, 2017), but we currently do not have data on whether these risk factors are elevated among the increasing population of competitive online gaming participants.…”
Section: Discussionmentioning
confidence: 99%
“…There is little research on the impacts of gaming on healthy lifestyle behavioral factors, including sedentary behavior, diet, and effective mitigation strategies. Given that obesity and associated adverse health issues are a critical priority for health policy makers globally, and there is evidence of growing sponsorship of esports and in-game product placement by harmful product categories such as alcohol, gambling, and junk food (Kelly and Van der Leij, 2020), research considering the well-being impacts of gaming is needed. Diet and metabolic risks have risen as leading drivers of diseases (Gakidou et al, 2017), but we currently do not have data on whether these risk factors are elevated among the increasing population of competitive online gaming participants.…”
Section: Discussionmentioning
confidence: 99%
“…What are the challenges to and opportunities for influencing the dietary behaviour of EAs through the online game ecosystem? Previous studies have shown the potential negative impact that online games have on dietary behaviour (Chan et al, 2022) and the range of marketing that is being targeted at EAs through the behavioural ecology (Elasri-Ejjaberi et al, 2020;Kelly and Gerrish, 2019). The influence of playing online games on food choices has also been explored (Cronin and McCarthy, 2011).…”
Section: Emerging Adult Gamers and Their Dietmentioning
confidence: 99%
“…Furthermore, there is an increasing amount of advertising and Emerging adult gamers and their diet sponsorship by the food industry throughout game spaces, which has seen the benefits of using online game channels to reach EAs who are difficult to engage by traditional channels (Elasri-Ejjaberi et al, 2020;Pollack et al, 2020). Examples of food and energy drink advertising can be found through in-game placement, sponsorship of esports tournaments, sponsorship of players and microcelebrities and advertising on digital channels (Kelly and Gerrish, 2019). Consequently, EA gamers are potentially compounding a sedentary activity with exposure to food marketing, which also impacts consumption (Bragg et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…To “close the loop”, this study evaluates the implemented intervention by measuring awareness levels, with the prediction that increasing awareness is a prerequisite for shifting attitudes and behaviour, as well as enhancing knowledge. This also builds on the extensive research in psychology, which suggests that simply being exposed to information, referred to as the mere exposure effect (Janiszewski, 1993), in itself can generate attitude and behaviour change (Kelly and Van der Leij, 2021). However, while the mere exposure effect has been explored in social marketing (Kouchaki and Jami, 2013), its role has rarely been studied within TSR (see, for exception, Mattila et al , 2016).…”
Section: Introductionmentioning
confidence: 98%